The Meaning of Work and Organizational Commitment of Generation Z Employees - Gagola, Auradini; Prapunoto, Susana (GoAcademica Research & Publishing, 2024)
This paper aims to determine the relationship between work meaningfulness and organizational commitment. The subjects in this research were 52 participants. The measuring instruments used are The Work and Meaning Inventory (WAMI) and the Organizational Commitment Scale. The collected data was processed using the Pearson Product Moment correlation test. The results of hypothesis testing show that there is a positive and significant relationship between the meaning of work and organizational commitment, meaning that if employees have a higher work meaning value, the higher their organizational commitment, as well as if employees have a lower work meaning value, the lower their organizational commitment.